Improving learners Mathematics problem solving skills and strategies in the intermediate phase : a case study of primary school in Lebopo Circuit - Raoano, Malesela Joel (University of Limpopo, 2016)
The purpose of this study was to examine learners’ mathematical word problem solving skills and strategies in Intermediate Phase. The study was prompted by Grade 6 learners’ poor performance in the cognitive area, non-routine mathematical word problems, as revealed in Annual National Assessment reports of 2011, 2012, 2013 and 2014. The study followed action research collaborative method involving 26 Grade 6 learners and their mathematics educator. The school is a rural primary school categorised under quintile two. Problem solving theory by Polya (1957) guided the study in answering three research questions: What are the challenges faced by Grade 6 learners in solving word problems? What are Grade 6 learners’ strategies in solving word problems? How can learners’ problem solving skills and strategies focusing on word problems be improved? Data were collected in a routine structured process: pre-intervention phase, intervention phase and post-intervention phase. Analysis was made through the development of a system of categorisation of learners’ responses. The four principles of problem solving by Polya (1957) namely, the way learners understand the problem, how they devise the plan, how they carry out the plan and the manner in which they look back guided the analysis. The findings of the study revealed that the strategies introduced assisted learners in making sense of the word problems and finally proceeding towards an adequate solution. It was also found out that the learners lacked the ability to read with understanding; the problem being their lack of competence in the language of learning and teaching. The skills which learners also lacked when solving word problems were identified as arithmetic skills and reflective skills.
Thesis (M. Ed. (Mathematics Education)) -- University of Limpopo, 2016.
Keywords: Leaners; Mathematics word problem solving skills; Children literature in mathematics education; Mathematics - Remedial teaching.